Fielding baseball skills and drills - American Baseball Coaches Association (Champaign Human Kinetics, 2001)
Fielding is one of three tapes in the ABCA's Baseball Skills & Drills video series. Hitting and Baserunning and Pitching and Catching as well as a comprehensive companion book titled Baseball Skills & Drills provide a superb set of instructional tools for players and coaches.
With 1 converted disc.
VHS format.
In English.
Keywords: Baseball